Running injuries in the participants of Ljubljana Marathon - Vitez Luka; Zupet Petra; Zadnik Vesna; Drobnič Matej (Sciendo, 2017)
The aim of our study was to determine the self-reported incidence and prevalence of running-related injuries among participants of the 18th Ljubljana Marathon, and to identify risk factors for their occurrence.